Measuring intra-party democracy : a guide for the content analysis of party statutes with examples from hungary, Slovakia and Romania - von dem Berge, Benjamin (SpringerBriefs in Political Science, 2013)
This book presents an integrated approach to measuring the level of intra-party democracy through deductive and standardized content analysis of party statutes. Following the two main criteria of intra-party democracy - inclusiveness and decentralization - three main categories of intra-party democracy are theoretically derived: members' rights, organizational structure and decision-making. On the basis of theoretical considerations further sub-categories and individual items are deduced from these main categories and put together into a comprehensive coding scheme. Furthermore, precise coding instructions are presented. Since it is the ultimate aim of this book to present an approach to measuring the level of intra-party democracy for any party statute and to express this in numerical terms, the final step is the quantification of the coded data and the calculation of a numeric measure of intra-party democracy. A numeric value of intra-party democracy can be calculated for any statute of any political party. Furthermore, empirical examples from Hungary, Slovakia and Romania are presented.